Analysis of Perception of Struggles in Finding a Job for Fresh Graduates at the College Level - Festi Zulfaturrohmah; Naila Chasanah; Natal Kristiono; Lyna Rahma Yulianty (Universitas Negeri Semarang, 2025)
This study aims to identify and analyze the perceptions of struggles experienced by fresh graduates in finding employment, focusing on both internal and external factors that affect their experiences. Data were collected through a questionnaire distributed to 34 alums of the Faculty of Social and Political Sciences who graduated between 2020 and 2024, as well as in-depth interviews with four selected informants. The results showed that 72% of respondents had work experience; however, 48% of them did not secure a job immediately after graduation. Factors that affect difficulties in job search include lack of work experience, company-set qualification limitations, and low soft skills of respondents. In addition, 56% of respondents reported that the uncertainty of their post-graduation future is a source of anxiety, which is exacerbated by social pressures from their surrounding environment and comparisons with the achievements of their peers. Most respondents (80%) stated that they struggle to find a job, even when applying for positions that do not align with their field of study. Adaptations made by fresh graduates include applying for entry-level jobs, expanding their professional relationships, and continuing their studies to the S2 level. These findings offer valuable insights for universities, companies, and educational institutions on supporting the transition of recent graduates into an increasingly competitive workforce.